Persepsi Masyarakat Dalam Penanganan Konflik Tanah Antara Ohoi Kelanit dan Ohoi Loon Pada Kabupaten Maluku Tenggara - Tupessy, Imanuel Jelles Izak; Tuanaya, Wahab; Latuconsina, Nurainy (Journal of Government Science Studies, 2024)
This research is to analyze community perceptions in handling land conflicts between ohoi kelanit and ohoi loon in kei kecil sub-district, southeast maluku. The research location is Ohoi Kelanit and Ohoi Loon villages. The resource persons in this research are customary chiefs and community leaders. The data source in this research uses descriptive qualitative research data.The results of this study indicate that the thing that causes land disputes in the kei kecil sub- district of southeast maluku district between kelanit village and loon village is due to the construction of a welcome gate that has crossed the petuanan boundary. The role of the customary chief and community leaders in resolving land disputes is as a peace judge by summoning the parties related to the land dispute. While the obstacles that occur in the settlement of land disputes in Kelanit and Loon villages are that there are small groups that do not attend the settlement of land disputes.